Blind Visionaries and Cheese-Eating Sceptics: The Place of Lived Religion in Disability History - Blackie, Daniel; Kuuliala, Jenni; Miettinen, Riikka; Perk, Godelinde Gertrude (Stockholm University Press, 2026)
This article advocates for two things: first, that religion be a central focus of disability studies, and second, that the study of disability history pay greater attention to the role of lived religion. It highlights how disability—understood as a culturally shaped form of difference—and lived religion—the everyday practice of belief—intersect as embodied experiences. Although scholars have explored how lived religion shapes gender and social status in (pre)modernity and how disability appears in medieval charity and hagiography, the relationship between early modern and nineteenth-century disability and religion remains understudied. Using fifteenth- and nineteenth-century European case studies, this article demonstrates how approaching disability history through lived religion reveals shifting margins and the meaning-making resources available to disabled people. This approach offers a richer, more nuanced understanding of their experiences and social roles in historical contexts.